APLIKASI PENINGKATAN CITRA BERBASIS OPEN SOURCE (STUDI KASUS: GNU OCTAVE) - Ardymulya Iswardani; Wahyu Hidayat (Universitas Muhammadiyah Semarang, 2018)
Main problem of this study is to implement the image enhancement techniques to mammographic image of breast cancer. This study aims to develop an image enhancement application using GNU Octave on open source platform operating system. At the beginning we used eight sample mammographic image with normal tissues and positive cancer. The process continued to convert the pgm format to jpg. This change needed, hence the negative image function and histogram equalization function can applied. Result of this research showed that visual quality affected by density level of the breast tissue of the patient. Density level with fatty showed better visual than both glandular and dense.This research conclude that the application of image enhancement using GNU Octave can be applied to mammographic image. Keywords: Mammographic, Image Enhancement, GNU Octave, Debian, Open Source